A arte do teatro do mamulengo na era digital. - Silva, Valéria Gomes de Barros e (2021)
The mamulengos theater is a traditional cultural, in the citys Glória do Goitá, Carpina, Lagoa de Itaenga, Vicência, Ferreiros, Nazaré da Mata, Tracunhaém, Itaquitinga, manifestation from the backlands of Pernambuco. Used as entertainment, the puppets use humor to make social criticism. In the digital era, culture and technology are intertwined. On one hand, culture preserves traditional knowledge. On the other, through digital tools, a world of possibilities for cataloging and publicizing the work of these mamulengo artists. The present report registers the formation and construction processes of Mamulengo Arteiro, a channel registered in the You Tube platform, where a reverberation work of the popular culture of the Mamulengos theater is done. The project was created using as main tool the Design Thinking and the audiovisual product was mostly made in some cities of the Northern Forest Zone of Pernambuco. For theoretical foundation of the work were used authors such as Tim Brown (2017), John Howkins (2013), Othon Jambeiro (2012) and Franco Jazielo. (2003). The Mamulengo Arteiro places the traditional knowledge within the circuit of the creative sectors of today.